Identification of strategy implementation influencing factors and their effects on the performance - Alharthy, Abdullah H.; Rashid, Hamad; Pagliari, Romano; Khan, Faisal (International Journal of Business and Social Science, 2017)
This paper investigates the factors that influence strategy execution in service organisations within both public and private sectors. The successful execution of the strategy is the key survival asset of the organisation. Many organisations could not maintain their competitive advantages, in spite of the existing process of drafting a strong strategy, due to lack of achievement in the strategy implementation stage. Leaders and top management of organisations must pay more attention to strategy implementation due to the higher failure rates that occur at this stage. For that, successful strategy implementation requires a better understanding of the relevant influencing factors that dictate that implementation’s outcomes. The existing literature does not provide a rigorous and structured conceptualisation of these factors, or their influence on strategy implementation. Accordingly, we precisely explored the mechanisms and interdependent abilities of such factors and their impact to address the gap. In addition, this paper presents many factors, which usually are neglected and cause failure or effect on the efficiency severity industry. This article also shows how some factors are more important in certain industry and l ess important in other industry in the Middle East.
Keywords: Strategy Implementation; Strategy Execution; Strategy implementation failure/success; Key